Zirconia ceramic material and preparation method thereof, and electronic equipment
By adding niobium oxide to the zirconia ceramic material and forming a niobium oxide layer, the phase transformation of zirconia is induced by cosintering technology to form a reinforced layer with high single-clinic phase content, solving the problem of yttrium oxide stabilizing zirconia ceramic back cover prone to cracking, significantly improving the strength and impact resistance of the material.
Patent Information
- Application Number
- CN202210899248.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-28
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-07-28
AI Technical Summary
The existing yttrium oxide-stabilized zirconia ceramic back cover is prone to cracks when it is dropped, which cannot meet the material strength requirements of mobile smart devices.
By adding 1 mol% to 4.8 mol% of niobium oxide to the zirconia ceramic material and forming a niobium oxide layer on the surface, the phase transformation of zirconia is induced by cosintering technology to form a reinforced layer with a high single-clinic phase content.
It effectively improves the strength of zirconia ceramic materials, increases the ability to resist damage to mechanical collisions, and meets the strength requirements of the back cover material of mobile smart devices.
Smart Images

Figure CN117510201B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of zirconium oxide ceramic materials. Background Art
[0002] At present, with the advent of the 5G era, new requirements have been put forward for the back cover materials of mobile smart devices, especially in terms of the signal transmission performance of the materials. Traditional metal materials will produce electromagnetic shielding effects and cannot meet the requirements. Zirconia ceramic materials are increasingly used due to their excellent mechanical properties, warm feel, and excellent signal penetration performance.
[0003] Yttria-stabilized zirconia ceramic material, as the back cover material of mobile smart devices, has high requirements for performance. However, the existing yttria-stabilized zirconia ceramic back cover is prone to cracks when dropped. Therefore, it is necessary to develop a ceramic material with higher strength to meet the usage requirements of mobile smart devices. Summary of the invention
[0004] In view of this, the present application provides a zirconia ceramic material and a preparation method thereof. The zirconia ceramic material has higher strength than the zirconia ceramic material in the prior art and can meet the strength requirements of the back cover of a mobile smart device for the material.
[0005] The present invention provides a zirconia ceramic material, wherein the ceramic material comprises 1 mol% to 4.8 mol% of niobium oxide and 95.2 mol% to 99 mol% of phase-stable zirconia ceramic; the ceramic material comprises a matrix layer and at least one strengthening layer adjacent to the matrix layer; the matrix layer is a phase-stable zirconia ceramic, the matrix layer comprises monoclinic zirconia and tetragonal zirconia, and the weight percentage of the monoclinic phase in the matrix layer accounts for 0.1 to 8% of the matrix layer ceramic; the strengthening layer comprises niobium oxide, monoclinic zirconia and tetragonal zirconia, the monoclinic phase content in the strengthening layer is greater than the monoclinic phase content in the matrix layer, the monoclinic phase content in the strengthening layer accounts for 5 to 80% of the weight percentage of the strengthening layer ceramic material, and the thickness of the strengthening layer is 0.5 to 25 μm.
[0006] Optionally, the content of the monoclinic phase in the matrix layer is 1% to 70% of the content of the monoclinic phase in the strengthening layer.
[0007] Optionally, the zirconia ceramic in the matrix layer is a phase-stable zirconia ceramic, which contains phase-stable oxides, and the phase-stable oxides include one or more of magnesium oxide, yttrium oxide, calcium oxide, strontium oxide, and cerium oxide.
[0008] Preferably, the phase-stabilized zirconia ceramic in the matrix layer comprises 1 to 10 mol % of phase-stabilized oxides and 90 to 99 mol % of zirconia.
[0009] Preferably, the thickness of the strengthening layer is 0.5-15 μm.
[0010] Preferably, the ceramic material composition comprises 1.8 mol% to 4.8 mol% of niobium oxide and 95.2 mol% to 98.2 mol% of phase-stabilized zirconia ceramic.
[0011] Preferably, the weight percentage of the monoclinic phase in the strengthening layer is 5-70%, and the weight percentage of the monoclinic phase in the matrix layer is 0.1-6%.
[0012] The present invention provides a method for preparing the above-mentioned zirconium oxide ceramic material, comprising the following steps:
[0013] (1) forming a zirconia ceramic raw material into a ceramic matrix blank, and sequentially performing a degreasing process and a first sintering process on the ceramic matrix blank to obtain a ceramic part;
[0014] (2) forming a niobium oxide coating on at least part of the surface of the ceramic part obtained in step (1) by magnetron sputtering; (3) performing a second sintering on the ceramic part having the niobium oxide coating on the surface obtained in step (2) to obtain the above-mentioned zirconium oxide ceramic material.
[0015] Optionally, in step (1), the first sintering temperature is 800° C.-1400° C., and the time is 0.5-4 h.
[0016] Optionally, the magnetron sputtering conditions in step (2) are: using metal niobium as a target and performing magnetron sputtering in an oxygen environment.
[0017] Optionally, in step (3), the second sintering temperature is 800°C-1450°C, and the time is 1-6h.
[0018] The present invention further provides an electronic device, wherein at least some components of the electronic device are made of the above-mentioned zirconium oxide ceramic material.
[0019] The inventor of the present invention has found through a large number of experiments that when niobium oxide and zirconium oxide ceramics are co-sintered to modify zirconium oxide ceramics, the pentavalent niobium ions in the niobium oxide layer partially replace the tetravalent zirconium ions in the zirconium oxide, resulting in a reduction in oxygen vacancies inside the tetragonal zirconium oxide, thereby inducing part of the tetragonal zirconium oxide in the zirconium oxide ceramic to transform into a monoclinic phase, causing volume expansion of about 3%-5%. The volume expansion caused by the phase transformation forms a compressive stress layer with a certain thickness on the surface of the ceramic. The presence of the compressive stress layer will inhibit the generation or propagation of cracks when the ceramic is impacted by external forces. This means that when a mechanical collision occurs, the zirconium oxide ceramic requires a greater collision force to be damaged, thereby effectively improving the strength of the zirconium oxide ceramic. Therefore, the strengthening layer of the zirconia ceramic of the present application is achieved by inducing a phase transformation of zirconia through a niobium oxide layer, and the monoclinic phase content in the strengthening layer is greatly increased relative to the monoclinic phase content in the matrix layer. The weight percentage of the monoclinic phase in the strengthening layer is 5 to 80% of the ceramic material of the strengthening layer, while the weight percentage of the monoclinic phase in the matrix layer where no chemical phase change occurs is 0.1 to 8% of the matrix layer ceramic. The monoclinic ceramic content in the matrix layer is 1% to 70% of the monoclinic ceramic content in the strengthening layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic diagram of the structure of the zirconia ceramic material prepared in Example 1 of the present application.
[0021] Figure 2 This is a SEM scanning electron microscope photograph of the zirconia ceramic material prepared in Example 3 of the present application.
[0022] The reference numerals are as follows: 1 - reinforcement layer; 2 - matrix layer. DETAILED DESCRIPTION
[0023] The technical solution of the present application is described in detail below with reference to the accompanying drawings.
[0024] The present application provides a zirconium oxide ceramic material, which comprises a matrix layer 2 and at least one strengthening layer 1 adjacent to the matrix layer 2. Preferably, Figure 1 As shown, there are two reinforcement layers 1 adjacent to the ceramic material and the matrix layer.
[0025] The present invention provides a zirconia ceramic material, wherein the ceramic material comprises 1 mol% to 4.8 mol% of niobium oxide and 95.2 mol% to 99 mol% of phase-stable zirconia ceramic; the ceramic material comprises a matrix layer and at least one strengthening layer adjacent to the matrix layer; the matrix layer is a phase-stable zirconia ceramic, the matrix layer comprises monoclinic zirconia and tetragonal zirconia, and the weight percentage of the monoclinic phase in the matrix layer accounts for 0.1 to 8% of the matrix layer ceramic; the strengthening layer comprises niobium oxide, monoclinic zirconia and tetragonal zirconia, the monoclinic phase content in the strengthening layer is greater than the monoclinic phase content in the matrix layer, the monoclinic phase content in the strengthening layer accounts for 5 to 80% of the weight percentage of the strengthening layer ceramic material, and the thickness of the strengthening layer is 0.5 to 25 μm.
[0026] The crystal phase of zirconia ceramics originally contains monoclinic ceramics and tetragonal ceramics. When niobium oxide and zirconia ceramics are co-sintered to modify zirconia ceramics, the pentavalent niobium ions in the niobium oxide layer partially replace the tetravalent zirconium ions in zirconia, resulting in a reduction in oxygen vacancies inside the tetragonal zirconia, which in turn induces some of the tetragonal zirconia in the zirconia ceramics to transform into a monoclinic phase, causing volume expansion of about 3%-5%. The volume expansion caused by the phase transition forms a compressive stress layer with a certain thickness on the surface of the ceramic. The presence of the compressive stress layer will inhibit the generation or propagation of cracks when the ceramic is impacted by external forces. This means that when a mechanical collision occurs, the zirconia ceramics require a greater collision force to break, thus effectively improving the strength of the zirconia ceramics. Therefore, the strengthening layer of the zirconia ceramic of the present application is converted from the niobium oxide layer and the zirconia ceramic through chemical reaction, and the content of monoclinic ceramic in the strengthening layer is greatly increased relative to the content of monoclinic ceramic in the matrix layer. The weight percentage of monoclinic ceramic in the strengthening layer is 5 to 80% of the ceramic material of the strengthening layer, while the weight percentage of monoclinic ceramic in the matrix layer where basically no chemical phase change occurs is 0.1 to 8% of the ceramic material of the matrix layer.
[0027] like Figure 2 As shown in the figure, because the zirconium oxide ceramic particles in the strengthening layer with a higher monoclinic phase content are larger, while the zirconium oxide ceramic particles in the matrix layer with a lower monoclinic phase content are relatively small, it can be clearly seen from the figure that there is a boundary between the strengthening layer and the matrix layer. According to the size test of the electron microscope photo, the depth of the strengthening layer is 7 microns.
[0028] Optionally, the content of monoclinic ceramics in the matrix layer is 1% to 70% of the content of monoclinic ceramics in the strengthening layer.
[0029] The present invention can change the monoclinic phase content and phase transition depth on the ceramic surface by controlling the molar percentage of niobium oxide in the material and coordinating the control of the monoclinic phase content in the matrix ceramic. It can also change the monoclinic phase content and phase transition depth on the ceramic surface by changing the monoclinic phase content in the matrix ceramic. It can also change the monoclinic phase content and phase transition depth on the ceramic surface by adjusting the molar percentage of niobium oxide and the monoclinic phase content in the matrix layer at the same time.
[0030] The inventors of the present invention have found that although a zirconia ceramic material with a thicker strengthening layer and a higher monoclinic phase content in the strengthening layer can be prepared by controlling the preparation method, the inventors of the present invention have found that the thickness of the strengthening layer is too thick, resulting in a decrease in the strength of the ceramic product. The inventors of the present invention believe that there are many phase variables inside the ceramic, which will produce uneven stress distribution inside the sintered body, thereby causing a decrease in its strength and failing to meet the requirements of industrial products. If the thickness of the strengthening layer is too thin, the strength enhancement effect on the ceramic material is too weak and cannot meet the strength requirements of industrial products.
[0031] The zirconia ceramic can be phase-stable zirconia ceramics known in the art. The phase-stable zirconia ceramic contains phase-stable oxides. Optionally, the phase-stable oxides are one or more of magnesium oxide, yttrium oxide, calcium oxide, strontium oxide, and cerium oxide.
[0032] Preferably, the phase-stabilized zirconia ceramic in the matrix layer comprises 1 to 10 mol % of phase-stabilized oxides and 90 to 99 mol % of zirconia.
[0033] Preferably, the thickness of the strengthening layer is 0.5-15 μm.
[0034] Preferably, the ceramic material composition comprises 1.8 mol% to 4.8 mol% of niobium oxide and 95.2 mol% to 98.2 mol% of phase-stabilized zirconia ceramic.
[0035] Preferably, the weight percentage of the monoclinic phase in the strengthening layer is 5-70%, and the weight percentage of the monoclinic phase in the matrix layer is 0.1-6%.
[0036] The present invention provides a method for preparing the above-mentioned zirconium oxide ceramic material, comprising the following steps:
[0037] (1) forming a zirconia ceramic raw material into a ceramic matrix blank, and sequentially performing a degreasing process and a first sintering process on the ceramic matrix blank to obtain a ceramic part;
[0038] (2) forming a niobium oxide coating on at least a portion of the surface of the ceramic member obtained in step (1) by magnetron sputtering;
[0039] (3) The ceramic component with the niobium oxide coating on the surface obtained in step (2) is subjected to a second sintering to obtain the above-mentioned zirconium oxide ceramic material.
[0040] The present invention further provides an electronic device, wherein at least some components of the electronic device are made of the above-mentioned zirconium oxide ceramic material.
[0041] The electronic device includes a terminal device, specifically, a smart phone, a smart watch and other electronic devices.
[0042] The technical solution of the present application is described in detail below in multiple embodiments.
[0043] Example 1
[0044] (1) Forming of ceramic matrix blank: Yttria-stabilized zirconia injection molding feed is put into an injection molding machine, and a ceramic matrix blank is prepared by injection molding. The injection molding conditions are: injection molding temperature is 210°C, injection molding pressure is 100MPa, and holding pressure is 100MPa. Degreasing treatment: The degreasing conditions are: heating from room temperature to 150°C at a heating rate of 2°C / min, keeping at 150°C for 1h, heating from 150°C to 400°C at a heating rate of 0.15°C / min, keeping for 2h, and then heating from 400°C to 450°C at a heating rate of 0.8°C / min, and keeping for 2h.
[0045] Sintering conditions: heating to 1400°C at a heating rate of 1.5°C / min, keeping the temperature for 2 hours, and then cooling naturally to room temperature to obtain a ceramic matrix, wherein the content of the phase-stable oxide yttria in the yttria-stabilized zirconia is 3 mol%, and the content of zirconium oxide is 97 mol%, to obtain a ceramic part;
[0046] (2) The ceramic part prepared in step (1) is subjected to surface magnetron sputtering treatment, with niobium as the target material. Magnetron sputtering is carried out in an oxygen environment, and a niobium oxide layer with a thickness of 0.1 μm is deposited on the surface of the ceramic. The corresponding molar percentage of niobium oxide in the zirconia ceramic material is 1.5 mol%.
[0047] (3) Sintering the ceramic deposited piece with niobium oxide deposited thereon obtained in step (2) to obtain a surface-strengthened zirconia ceramic; the sintering temperature is 1400° C., and the maximum high temperature holding time is 2 hours.
[0048] Example 2
[0049] The difference from Example 1 is:
[0050] (2) A niobium oxide layer with a thickness of 0.15 μm is deposited on the ceramic surface. The corresponding molar percentage of niobium oxide in the zirconia ceramic material is 1.8 mol%.
[0051] Example 3
[0052] The difference from Example 1 is:
[0053] (2) A niobium oxide layer with a thickness of 0.2 μm is deposited on the ceramic surface. The corresponding molar percentage of niobium oxide in the zirconia ceramic material is 3 mol%.
[0054] Example 4
[0055] The difference from Example 1 is:
[0056] (2) A niobium oxide layer with a thickness of 0.25 μm is deposited on the ceramic surface. The corresponding molar percentage of niobium oxide in the zirconia ceramic material is 3.5 mol%.
[0057] Example 5
[0058] The difference from Example 1 is:
[0059] (2) A niobium oxide layer with a thickness of 0.3 μm is deposited on the ceramic surface. The corresponding molar percentage of niobium oxide in the zirconia ceramic material is 3.8 mol%.
[0060] Comparative Example 1
[0061] The difference from Example 1 is that the zirconia ceramic material is not subjected to step (2) and step (3), that is, the ceramic is not subjected to strengthening layer treatment.
[0062] Comparative Example 2
[0063] The difference from Example 1 is that the yttria-stabilized zirconia ceramic material was not subjected to step (3). That is, the zirconia ceramic was plated with a niobium oxide layer but not sintered.
[0064] Comparative Example 3
[0065] The difference from Example 1 is that a niobium oxide layer with a thickness of 0.05 μm is deposited on the ceramic surface, and the corresponding molar percentage of niobium oxide in the zirconium oxide ceramic material is 0.2 mol%.
[0066] Comparative Example 4
[0067] The difference from Example 1 is that a niobium oxide layer with a thickness of 0.5 μm is deposited on the ceramic surface, and the corresponding molar percentage of niobium oxide in the zirconium oxide ceramic material is 5 mol%.
[0068] The following tests were performed on the zirconia ceramic materials obtained in the above embodiments and comparative examples:
[0069] (1) Monoclinic phase content: measured by X-ray polycrystal diffraction analyzer;
[0070] (2) Depth of strengthening layer: measured by SEM scanning;
[0071] (3) Four-point bending strength test: measured using a universal mechanical testing machine, the test standard refers to GBT6569-2006;
[0072] (4) Drop ball test: Take 10 pieces of zirconia ceramic materials with a thickness of 0.55mm and a length and width of 50mm for the drop ball test. The drop ball test uses a 32g steel ball, which starts to fall freely from a height of 5cm. If the sample does not break after impact, continue to increase the steel ball height by 5cm and continue the test until the ceramic breaks. The height at this time is recorded as the drop ball height of the ceramic material. The drop ball test height is the average value of the above 10 phase-stable zirconia ceramic material samples and is recorded as the drop ball test height of the sample.
[0073] Table 1 Summary of test results of ceramic materials obtained in various embodiments and comparative examples
[0074]
[0075] The four-point bending strength of Examples 1-5 of the present invention is greater than or equal to 1200 MPa, and the average drop ball test height is greater than 20 cm. Compared with Comparative Examples 1-4, the four-point bending strength and the drop ball test height are improved. The additional strengthening layer on the ceramic surface effectively improves the material's bending strength and resistance to drop ball damage, thereby improving the material's performance.
[0076] Comparative Example 2 of the present invention adopts a yttria-stabilized zirconia with a yttria content of 3 mol% and a zirconium oxide content of 97 mol%. Although a niobium oxide layer is plated on the surface of Comparative Example 2, the zirconia ceramic is not sintered, so no chemical reaction occurs, no strengthening layer is formed, and the ceramic strength is not improved. In contrast, in Examples 1-5, niobium oxide and zirconia ceramic are sintered, and the niobium oxide reacts chemically with the phase-stabilized zirconia, so that the niobium oxide converts part of the tetragonal zirconia in the zirconia ceramic into a monoclinic phase, causing volume expansion, thereby improving the strength of the zirconia ceramic material. From the test results, it can be seen that both the four-point bending strength and the height of the drop ball test are improved.
[0077] It can be seen from Comparative Example 3 that the thickness of the strengthening layer is too thin, and the strength enhancement effect on the ceramic material is too weak to meet the strength requirements of industrial products.
[0078] From Comparative Example 4, it can be seen that the thickness of the strengthening layer is too thick, the strength of the ceramic product decreases, and it does not meet the requirements of industrialized products. The inventors of the present invention believe that there are many phase variables inside the ceramic, which produces uneven stress distribution inside the sintered body, thereby causing its strength to decrease.
[0079] The above is an exemplary embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A zirconium oxide ceramic material, characterized in that: The ceramic material composition comprises 1 mol% to 4.8 mol% of niobium oxide and 95.2 mol% to 99 mol% of phase-stable zirconia ceramics; the ceramic material comprises a matrix layer and at least one strengthening layer adjacent to the matrix layer; the matrix layer is a phase-stable zirconia ceramic, the matrix layer comprises monoclinic zirconia and tetragonal zirconia, and the weight percentage of the monoclinic phase in the matrix layer is 0.1 to 8% of the matrix layer ceramic; the strengthening layer comprises niobium oxide, monoclinic zirconia and tetragonal zirconia, the monoclinic phase content in the strengthening layer is greater than the monoclinic phase content in the matrix layer, the monoclinic phase content in the strengthening layer accounts for 5 to 70% of the weight percentage of the strengthening layer ceramic material, and the thickness of the strengthening layer is 0.5 to 15 μm; The method for preparing the zirconium oxide ceramic material comprises the following steps: (1) forming a zirconia ceramic raw material into a ceramic matrix blank, and sequentially performing a degreasing process and a first sintering process on the ceramic matrix blank to obtain a ceramic part; (2) forming a niobium oxide coating on at least a portion of the surface of the ceramic member obtained in step (1) by magnetron sputtering; (3) The ceramic piece having the niobium oxide coating on the surface obtained in step (2) is subjected to a second sintering to obtain the zirconium oxide ceramic material.
2. The zirconia ceramic material according to claim 1, wherein the monoclinic phase content in the matrix layer is 1% to 70% of the monoclinic phase content in the strengthening layer.
3. The zirconia ceramic material according to claim 1, characterized in that: The zirconia ceramic in the matrix layer is a phase-stable zirconia ceramic, which contains phase-stable oxides. The phase-stable oxides include one or more of magnesium oxide, yttrium oxide, calcium oxide, strontium oxide and cerium oxide.
4. The zirconia ceramic material according to claim 3, characterized in that: Based on the total mass of the matrix layer, the phase-stabilized zirconia ceramic in the matrix layer contains 1 to 10 mol % of phase-stabilized oxide and 90 to 99 mol % of zirconia.
5. The zirconia ceramic material according to claim 1, characterized in that: The ceramic material composition comprises 1.8 mol% to 4.8 mol% of niobium oxide and 95.2 mol% to 98.2 mol% of phase-stabilized zirconium oxide ceramic.
6. The zirconia ceramic material according to claim 1, characterized in that: The weight percentage of the monoclinic phase in the matrix layer is 0.1-6%.
7. A method for preparing a zirconia ceramic material, characterized in that: The following steps are involved: (1) forming a zirconia ceramic raw material into a ceramic matrix blank, and sequentially performing a degreasing process and a first sintering process on the ceramic matrix blank to obtain a ceramic part; (2) forming a niobium oxide coating on at least a portion of the surface of the ceramic member obtained in step (1) by magnetron sputtering; (3) The ceramic component having a niobium oxide coating on the surface obtained in step (2) is subjected to a second sintering to obtain the zirconium oxide ceramic material according to any one of claims 1 to 6.
8. The preparation method according to claim 7, characterized in that: In step (1), the first sintering temperature is 800°C-1400°C, and the time is 0.5-4 h.
9. The preparation method according to claim 7, characterized in that: The magnetron sputtering conditions in step (2) are: using metal niobium as a target and performing magnetron sputtering in an oxygen environment.
10. The preparation method according to claim 7, characterized in that: In step (3), the second sintering temperature is 800°C-1450°C, and the time is 1-6 h.
11. An electronic device, characterized in that: At least some components of the electronic device are made of the zirconium oxide ceramic material as described in any one of claims 1-6.
Citation Information
Patent Citations
Method for making functional ceramic films on ceramic materials
CN102596853A